Wien Möbel. (Wien : Wiener Secession, 1989)
Blau, Luigi ; Bretterbauer, Gilbert ; Burghardt, Andreas ; Culen, Stefan ; Czech, Hermann ; Ebenberger, Erwin ; Exner, Thomas ; Frank, Irmgard ; Katzberger, Paul ; Billy, Karin ; Kneissl, Franz Eberhard ; Kogler, Peter ; Krischanitz, Adolf ; Loudon, Michael ; etc.
Ausstellung Wien Möbel / Exhibition Vienna Furniture, Wiener Secession, Wien, 7.6. - 16.7.1989
Duits & Engels
kunstcatalogus
Keywords: Wenen